Minimally invasive management of combined esophageal atresia with tracheoesophageal fistula and duodenal atresia: a comprehensive case report - Jung, Eunyoung (Frontiers in Pediatrics, 2023)
A newborn presented with a rare combination of esophageal atresia with tracheoesophageal fistula (EA/TEF) and duodenal atresia (DA), which was successfully managed using minimally invasive surgical techniques. The patient was a 1-day-old male for whom passing a feeding tube was infeasible and who had a double bubble sign on radiography. The neonate underwent a thoracoscopic ligation of the tracheoesophageal fistula (TEF) and a laparoscopic duodeno-duodenostomy on the same day, resulting in stabilized vital signs. Ten days after the initial operation, a thoracoscopic esophago-esophagostomy was successfully performed. The patient demonstrated full feeding capability and normal weight gain after the surgeries. The co-occurrence of EA/TEF and DA is a rare and complex anomaly. This case indicates that minimally invasive techniques can effectively manage this condition.